FLOW CYTOMETRIC AND DEMOGRAPHIC ANALYSIS OF T CELL ACUTE LYMPHOBLASTIC LEUKEMIA IN PAKISTANI POPULATION - Khawaja, MR; Allana, SS; Akbarali, AN; Adil, SN; Khurshid, M.; Pervez, S (Journal of Ayub Medical College Abbottabad, 2005)
Background: This study was carried out to analyze the proportion of T cell acute lymphoblastic leukemia (TALL) among all acute lymphoblastic leukemia (ALL) in Pakistani population and its correlation with the demographic features. Accuracy of cell surface markers used in flow cytometric analysis of the leukemic cells was also determined. Methods: Data of 209 consecutive cases of acute lymphoblastic leukemia (ALL) presenting between July 1995 and July 2003 was analyzed. Flow cytometry was performed on all ALL cases using the standard protocols. TALL markers included CD3, CD5 and CD7. Results: Proportion of TALL among known ALL Pakistani patients was 17.22%. Mean age of the TALL patients was 17.2 years. Proportion of TALL was higher in adults than in children (21.95% vs. 14.17%). Overall in this study there were more male patients affected by TALL (25/36 or 69.40%) than females (11/36 or 30.60%). The female to male ratio among TALL patients was 1:2.27. However, the proportion (%) of TALL in females was higher than males (18.96% vs. 15.82 %) i, e, 1.2:1. CD7 was found to be the most sensitive among both adults & children. It was positive in 94.4% of the TALL cases. Conclusion: Proportion of TALL among ALL in Pakistan is similar to that reported in this region, indicating a candidate association with geographical location and socioeconomic status. The reactivity of markers with TALL cells was similar to what we expected based upon literature. However, due to some aberrant and cross reactivity displayed by each marker, we strongly recommend a panel approach including B and myeloid markers to ensure a correct diagnosis of TALL. Keywords: Leukemia, T cell acute lymphoblastic leukemia (TALL), Flow Cytometry